2018
DOI: 10.1371/journal.pntd.0006932
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in dengue seroprevalence and force of infection in the urban paediatric population of Indonesia

Abstract: Understanding the heterogeneous nature of dengue transmission is important for prioritizing and guiding the implementation of prevention strategies. However, passive surveillance data in endemic countries are rarely adequately informative. We analyzed data from a cluster-sample, cross-sectional seroprevalence study in 1–18 year-olds to investigate geographic differences in dengue seroprevalence and force of infection in Indonesia. We used catalytic models to estimate the force of infection in each of the 30 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…find that the force of infection estimate obtained with model 1 variant PS fitted to average annual case notification data reported between 2008 and 2017 in Jakarta province (0.130 (95%CrI: 0.129-0.131)) is similar to the estimate obtained from seroprevalence data collected in 2014 in 30 urban subdistricts of Indonesia (0.14 (95%CI: 0.133-0.147))(5,25).We observed significant spatiotemporal heterogeneity in force of infection within Jakarta province, with long-term spatial clustering of both high and low transmission intensity subdistricts. Our analysis identified a hot-spot of dengue transmission in the southeast of Jakarta province and clustering of low transmission intensity in the region of Central Jakarta.Subdistrict population density was found to have a weak association with dengue transmission intensity, explaining approximately 5% of the variation in subdistrict force of infection estimates during the period of 2008-2017, with higher average annual force of infection associated with greater population densities (for details see SI sections 3.5 and Figure S8).…”
supporting
confidence: 69%
“…find that the force of infection estimate obtained with model 1 variant PS fitted to average annual case notification data reported between 2008 and 2017 in Jakarta province (0.130 (95%CrI: 0.129-0.131)) is similar to the estimate obtained from seroprevalence data collected in 2014 in 30 urban subdistricts of Indonesia (0.14 (95%CI: 0.133-0.147))(5,25).We observed significant spatiotemporal heterogeneity in force of infection within Jakarta province, with long-term spatial clustering of both high and low transmission intensity subdistricts. Our analysis identified a hot-spot of dengue transmission in the southeast of Jakarta province and clustering of low transmission intensity in the region of Central Jakarta.Subdistrict population density was found to have a weak association with dengue transmission intensity, explaining approximately 5% of the variation in subdistrict force of infection estimates during the period of 2008-2017, with higher average annual force of infection associated with greater population densities (for details see SI sections 3.5 and Figure S8).…”
supporting
confidence: 69%
“…collected in 2014 in 30 urban subdistricts of Indonesia (0.14 (95%CI: 0.133-0.147)) [5,25]. We observed significant spatiotemporal heterogeneity in force of infection within Jakarta province, with long-term spatial clustering of both high and low transmission intensity subdistricts.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 75%
“…Blue dashed line and shading shows the median and 95% credible interval province-level average annual force of infection in 2008-2017. FOI: force of infection.Boundaries were obtained from Wikimedia Commons under a CC-BY 3.0 NL license and converted to shapefile format using QGIS(25,26).…”
mentioning
confidence: 99%
“…These studies have shown that geographical information systems (GIS) techniques could provide helpful evidence for designing and implementing surveillance and targeted control measures. A recent study demonstrated evidence for spatial variation in dengue seroprevalence among Indonesian children at the national level [30]. However, this study did not clearly visualize and capture the variation within districts and was limited to urban settings.…”
Section: Introductionmentioning
confidence: 96%